Α4β2 nicotinic receptor status in Alzheimer's disease using 123I-5IA-85380 single-photon-emission computed tomography. Issue 4 (29th November 2006) - O'Brien, J T; Colloby, S J; Pakrasi, S; Perry, E K; Pimlott, S L; Wyper, D J; McKeith, I G; Williams, E D
Abstract : Background: Loss of the α4β2 nicotinic receptor subtype is found at autopsy in Alzheimer's disease. Objective: To investigate in vivo changes in this receptor using single-photon-emission CT (SPECT) with 123 I-5-iodo-3-[2(S)-2-azetidinylmethoxy] pyridine (5IA-85380), a novel nicotinic acetylcholine receptor ligand which binds predominantly to the α4β2 receptor. Methods: 32 non-smoking subjects (16 with Alzheimer's disease and 16 normal elderly controls) underwent 123 I-5IA-85380 and perfusion ( 99m Tc-hexamethylenepropyleneamine oxime (HMPAO)) SPECT scanning. Region of interest analysis was performed with cerebellar normalisation. Results: Significant bilateral reductions in nicotinic receptor binding were identified in frontal (left, p = 0.004; right, p = 0.002), striatal (left, p = 0.004; right, p = 0.003), right medial temporal (p = 0.04) and pons (p<0.001) in patients with AD compared to controls. There were no significant correlations with clinical or cognitive measures. The pattern of nicotinic binding significantly differed from that of perfusion in both patients with AD and controls. Both 123 I-5IA-85380 and 99m Tc-HMPAO SPECT imaging demonstrated similar diagnostic performance in correctly classifying controls and patients with AD. Conclusion: Using 123 I-5IA-85380 SPECT we found changes consistent with significant reductions in the nicotinic α4β2 receptor in cortical and striatal brain regions. This method could facilitate diagnosis and may be useful for monitoring progression of the disease and response to treatment in patients with AD and related diseases.